Response surface optimization of vibration level in diesel engine with biodiesel usage: a performance enhancement study / Muhammad Zikri Japri ... [et al.] - Japri, Muhammad Zikri; Mohd Sani, Mohd Shahrir; Jaliliantabar, Farzad; Arbintarso, Ellyawan Setyo (UiTM Press, 2024)
In this study, a single-cylinder direct-injection (DI) diesel engine was fueled by biodiesel. The Palm Oil Methyl Ester (POME), blended in amounts up to 20%, is tested at various engine speeds and loads to measure vibration level. Then, mathematical modeling was developed to relate the engine vibration level's responses to variables, including engine speed, load, and biodiesel blending percentage. Finally, all the numerical factors were calibrated using the proposed models. The significance of all factors in this study was demonstrated by the second peak of the engine's vibration, which contains a wealth of information about the excitations. Modeling results had previously shown that the significance of factors could vary according to the corresponding peaks of vibration in the engine. Meanwhile, the adjusted R2 of the developed model for vibration responses were 0.98, 0.87, 0.76, and 0.79, respectively. Further, the optimization results highlighted that utilizing a B20 fuel blend—a mixture of 20% biodiesel and 80% diesel fuel by volume—run at 2160 rpm with no load condition produced the best solution with the highest desirability value to satisfy all the responses. In summary, the study's findings showed that optimization should be considered while developing a new policy for using biofuel in internal combustion engines.